Freedom in the Dutch middle-field: Deriving discourse structure at the syntax-pragmatics interface - Schoenmakers, Gert-Jan (Glossa (London), 2020)
This paper experimentally explores the optionality of Dutch scrambling structures with a definite object and an adverb. Most researchers argue that such structures are not freely interchangeable, but are subject to a strict discourse template. Existing analyses are based primarily on intuitions of the researchers, while experimental support is scarce. This paper reports on two experiments to gauge the existence of a strict discourse template. The discourse status of definite objects in scrambling clauses is first probed in a fill-in-the-blanks experiment and subsequently manipulated in a speeded judgment experiment. The results of these experiments indicate that scrambling is not as restricted as is commonly claimed. Although mismatches between surface order and pragmatic interpretation lead to a penalty in judgment rates and a rise in reaction times, they nonetheless occur in production and yield fully acceptable structures. Crucially, the penalties and delays emerge only in scrambling clauses with an adverb that is sensitive to focus placement. This paper argues that scrambling does not map onto discourse structure in the strict way proposed in most literature. Instead, a more complex syntax of deriving discourse relations is proposed which submits that the Dutch scrambling pattern results from two familiar processes which apply at the syntax-pragmatics interface: reconstruction and covert raising.